2023
DOI: 10.3762/bjoc.19.65
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric tandem conjugate addition and reaction with carbocations on acylimidazole Michael acceptors

Abstract: We present here a stereoselective tandem reaction based on the asymmetric conjugate addition of dialkylzinc reagents to unsaturated acylimidazoles followed by trapping of the intermediate zinc enolate with carbocations. The use of a chiral NHC ligand provides chiral zinc enolates in high enantiomeric purities. These enolates are reacted with highly electrophilic onium compounds to afford densely substituted acylimidazoles. DFT calculations helped to understand the reactivity of the zinc enolates derived from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We have also demonstrated that asymmetric conjugate addition (ACA) formed metal enolates are compatible with more electrophilic onium compounds that comprise stabilized carbocations. 3 Importantly, carbocations serve as catalysts, 4 and provide access to structurally complex compounds that are not easily accessible with other electrophilic reagents. 5 However, high reactivity and instability of many carbocations precludes their application in metal catalyzed conjugate additions or reactions with organometallic nucleophiles.…”
mentioning
confidence: 99%
“…We have also demonstrated that asymmetric conjugate addition (ACA) formed metal enolates are compatible with more electrophilic onium compounds that comprise stabilized carbocations. 3 Importantly, carbocations serve as catalysts, 4 and provide access to structurally complex compounds that are not easily accessible with other electrophilic reagents. 5 However, high reactivity and instability of many carbocations precludes their application in metal catalyzed conjugate additions or reactions with organometallic nucleophiles.…”
mentioning
confidence: 99%
“…An enantioselective palladium-catalyzed three-component reaction of glyoxylic acid, sulfonamides, and aryltrifluoroborates toward synthetically useful α-arylglycine compounds is described by the Manolikakes group [ 11 ]. Moreover, Šebesta and co-workers report a facile stereoselective tandem reaction based on the asymmetric conjugate addition of dialkylzinc reagents to unsaturated acylimidazoles, followed by trapping of the intermediate zinc enolate with carbocations [ 12 ]. A practical one-pot synthesis of fluorescent pyrazolo[3,4- b ]pyridin-6-ones by reacting 5-aminopyrazoles with azlactones under solvent-free conditions, through subsequent elimination of a benzamide molecule in a superbasic medium, is described by the Fisyuk group [ 13 ].…”
mentioning
confidence: 99%